Prognostic assessment of estimated glomerular filtration rate by the new Chronic Kidney Disease Epidemiology Collaboration equation in comparison with the Modification of Diet in Renal Disease Study equation - Skali, Hicham; Uno, Hajime; Levey, Andrew S.; Inker, Lesley A.; Pfeffer, Marc A.; Solomon, Scott D. (The American heart journal, 2011)
Systematic reporting of estimated glomerular filtration rate (eGFR) using the Modification of Diet in Renal Disease (MDRD) Study equation is recommended for detection of chronic kidney disease and prediction of cardiovascular (CV) risk. The Chronic Kidney Disease Epidemiology Collaboration (CKD-EPI) equation is a newly developed and validated formula for eGFR that is more accurate at normal or near-normal eGFR. We aimed to assess the incremental prognostic accuracy of eGFR CKD-EPI versus eGFR MDRD in subjects at increased risk for CV disease. We performed a post hoc analysis of the VALIANT trial that enrolled 14,527 patients with acute myocardial infarction with signs and symptoms of heart failure and/or left ventricular systolic dysfunction. The eGFR MDRD and eGFR CKD-EPI were computed using age, gender, race, and baseline creatinine level. Patients were categorized according to their eGFR using each equation. To assess the incremental prognostic value of eGFR CKD-EPI, the net reclassification improvement was calculated for the composite end point of CV death, recurrent myocardial infarction, heart failure, or stroke. Twenty-four percent of the subjects were reclassified into a different eGFR category using eGFR CKD-EPI. The composite end point occurred in 33% of the subjects in this cohort. Based on eGFR CKD-EPI, subjects reclassified into a higher eGFR experienced fewer events than those reclassified into a lower eGFR (21% vs 43%). In unadjusted analyses, the composite end point risk in subjects with eGFR between 75 and 90 mL/min per 1.73 m 2 was comparable with the referent group (eGFR between 90 and 105) using eGFR MDRD (hazard ratio 1.1, 95% CI 0.9-1.2) but was significantly higher using eGFR CKD-EPI (hazard ratio 1.2, 95% CI 1.1-1.4). The net reclassification improvement for eGFR CKD-EPI over eGFR MDRD was 8.7%. The CKD-EPI equation provides more accurate risk stratification than the MDRD Study equation in patients at high risk for CV disease, including identification of increased risk at mildly decreased eGFR.